A Population‐Based Analysis of Outpatient Thyroidectomy: Safe and Under‐Utilized. (11th August 2021) - Noel, Christopher W.; Griffiths, Rebecca; Siu, Jennifer; Forner, David; Urbach, David; Freeman, Jeremy; Goldstein, David P.; Irish, Jonathan C.; Higgins, Kevin M.; Devon, Karen; Pasternak, Jesse D; Eskander, Antoine
Abstract : Objectives/Hypothesis: Performance of thyroidectomy on an outpatient basis has gained popularity although many jurisdictions have not shifted their practice despite a strong safety profile. We sought to assess the uptake and safety of outpatient thyroidectomy in Ontario. Study Design: Retrospective cohort study. Methods: This was a population‐based retrospecive cohort of adult patients undergoing hemithyroidectomy or total thyroidectomy between 1993 and 2017 in Ontario, Canada. Outpatient surgery was defined as discharge home on the same day of surgery. Outcomes of interest include 30‐day all cause death, hematoma, emergency department use, and readmission. To adjust for confounding, propensity scores were calculated. Logistic regression models with inverse probability of treatment weighting (IPTW) were then used to estimate the exposure‐outcome relationship. Results: The final cohort consisted of 81, 199 patients: 8, 442 underwent same day surgery and 72, 757 were admitted. The proportion of patients undergoing outpatient thyroidectomy increased overtime (2.3% in 1993–1994 to 17.8% in 2016–2017). Factors associated with higher odds of outpatient thyroidectomy included: younger age, less material deprivation, less comorbidities, and higher surgeon volume. The absolute number of deaths (≤5) and hematomas (64, 0.8%) in the outpatient cohort was low. After IPTW adjustment, patients with outpatient management had lower odds of neck hematoma (OR 0.73[95CI% 0.58–0.93)], but higher odds of emergency department use (OR 1.67[95%CI 1.56–1.79]). Conclusions: Outpatient thyroidectomy is not associated with an increased mortality risk. Less than one in five patients undergo outpatient thyroidectomy in Ontario, despite a well‐established safety profile. Level of Evidence: 3 Laryngoscope, 131:2625–2633, 2021